The control of the validity of an adoption constituted by a foreign authority and the requirement of a declaration of suitability: A question of legal security - Sánchez Cano, Mª Jesus (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
This paper will explain the most relevant aspects of the requirement of a declaration of suitability in international adoptions, regarding their effectiveness in Spain and their registration in the Spanish Civil Register. Such analysis will help to understand the position of the Directorate General of Legal Security and Public Trust, which in its Resolution (51st) of 8 February 2021, rejects the application for registration in the Spanish Civil Register of an adoption constituted in Equatorial Guinea respect to a minor national and resident in that country, according to Article 26.3 of the Spanish International Adoption Law as the Public Entity refuses to issue a certificate of suitability of the adoptive parents.
Keywords: intercountry adoption; declaration of suitability; application for registration